HGF-rs12536657 and Ocular Biometric Parameters in Hyperopic Children, Emmetropic Adolescents, and Young Adults: A Multicenter Quantitative Trait Study. (3rd February 2019) - Barrio-Barrio, Jesús; Bonet-Farriol, Elvira; Galdós, Marta; Noval, Susana; Pueyo, Victoria; Breeze, Charles E.; Santos, Jose Luis; Alfonso-Bartolozzi, Belén; Recalde, Sergio; Patiño-García, Ana
Abstract : Introduction . Even though ocular refractive state is highly heritable and under strong genetic control, the identification of susceptibility genes remains a challenge. Several HGF (hepatocyte growth factor) gene variants have been associated with ocular refractive errors and corneal pathology. Purpose . Here, we assess the association of an HGF gene variant, previously reported as associated with hyperopia, and ocular biometric parameters in a multicenter Spanish cohort. Methods . An observational prospective multicenter cross-sectional study was designed, including a total of 403 unrelated subjects comprising 188 hyperopic children (5 to 17 years) and 2 control groups: 52 emmetropic adolescents (13 to 17 years) and 163 emmetropic young adults (18 to 28 years). Each individual underwent a comprehensive eye examination including cycloplegic refraction, and topographic and ocular biometric analysis. Genomic DNA was extracted from oral swabs. HGF single nucleotide polymorphism (SNP) rs12536657 was genotyped. Genotypic, allelic, and logistic regression analyses were performed comparing the different groups. A quantitative trait association test analyzing several biometric parameters was also performed using generalized estimating equations (GEEs) adjusting for age and gender. Results . No association between rs12536657 and hyperopia was found through gender-adjusted logistic regression comparing the hyperopic children with either of the two control groups. Significant associations between mean topographic corneal curvature and rs12536657 for G/A (slope = +0.32; CI 95%: 0.04–0.60;p = 0.023 ) and A/A (slope = +0.76; CI 95%: 0.12–1.40;p = 0.020 ) genotypes were observed with the age- and gender-adjusted univariate GEE model. Both flat and steep corneal topographic meridians were also significantly associated with rs12536657 for the G/A and A/A genotypes. No association was found between rs12536657 and any other topographic or biometric measurements. Conclusions . Our results support a possible role for HGF gene variant rs12536657 in corneal curvature in our population. To our knowledge, this is the first multicenter quantitative trait association study of HGF genotypes and ocular biometric parameters comprising a pediatric cohort.